Application of Exponential Temperature Dependent Viscosity Model for Fluid Flow over a Moving or Stationary Slender Surface - Saddam Sultan Akbar; Meraj Mustafa (Mathematics, 2022)
The problem of laminar flow around a moving thin needle or slender surface with free stream velocity is analyzed when viscosity is supposed to have an exponential temperature dependency. Additionally, the temperature dependence in thermal conductivity is retained. Consideration of variable viscosity and thermal conductivity makes the governing equations coupled and non-linear. A self-similar solution of the problem is achieved, which depends on a parameter <semantics>θw</semantics>, which is the quotient of wall and ambient temperatures. A comparison of present findings is made with those of inversely linear temperature-dependent viscosity and constant viscosity cases. The size of the needle plays an important part in enhancing thermal boundary layer thickness. The expressions of skin friction coefficient and local Nusselt number in case of exponential temperature dependent viscosity are just derived in this study. An important observation is that computational results are qualitatively like those noticed for the case of inversely linear temperature dependency.